ANALISIS RISIKO PENDAPATAN USAHATANI LADA HITAM DI DESA KARET JAYA KECAMATAN BUAY PEMACA KABUPATEN OGAN KOMERING ULU SELATAN - Munajat, Endang Lastinawati, Sika Riana, Fifian Permata Sari, (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2025)
Pepper (Piper nigrum L.) plays an important role in the Indonesian economy. Although pepper farming has the potential to provide farmers with significant profits, it does not mean that it is without risks. This study aims to analyze the income and risks of pepper farming. The study was conducted in Karet Jaya Village, Buay Pemaca District, South OKU Regency. The location was determined purposively. The method used in this study was a survey method. The sampling method used in this study was a simple random sampling method, by taking 30 pepper farmers as samples. Income received from black pepper farming was calculated using the income formula, while income risk was calculated through a coefficient of variation analysis. The results showed that the average income of black pepper farming in Karet Jaya Village, Buay Pemaca District, South OKU Regency was Rp 3,342,479.00/year. Black pepper farming in Karet Jaya Village, Buay Pemaca District, South OKU Regency has a coefficient of variation CV of 0.009257176 ≤ 0.5 and an L value of ≥ 0, which means that black pepper farming avoids losses.